Organizational Culture and Pedagogical Management in Peru - Patiño-García, Lucia-Viviana; Zapata Ancajima, Juan Carlos; Luján-Vera, Priscila E.; García Vilela, Lucy Mariella; Aguirre Camarena, Richard Alejandro; Aguilar Soto, Ivett Violeta; Silva Juárez, Raquel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The purpose of the article was to determine the relationship between the organizational culture and the institutional management of the "Enrique López Albújar" Educational Institution, Piura. Work is worked under a quantitative approach, descriptive and correlational scope, 40 teachers participated as a sample. Among the results, it was found that there is no significant relationship between organizational culture and institutional management, which did not allow validating the research hypothesis; However, a significant relationship between norms and customs with institutional management was found; which concludes in compliance with the norms and good customs based on values.